Task-specific Human Capital and Organizational Inertia - Josse Delfgaauw; Otto H. Swank (Tinbergen Institute, 2014)
Employees' incentive to invest in their task proficiency depends on the likelihood that they will execute the same tasks in the future. Changes in tasks can be warranted as a result of technological progress and changes in firm strategy as well as from fine-tuning job design and from monitoring individuals' performance. However, the possibility of a change in tasks reduces employees' incentive to invest in task-specific skills. We develop a simple two-period principal-agent model showing that some degree of inertia benefits the principal. We then analyze how organizations can optimally combine several policies to approach the optimal degree of inertia. In particular, we consider the optimal mixture of (abstaining from) exploration, managerial vision, organizational task-specific investments, and incentive pay. Our analysis yields testable predictions concerning the relations between these organizational policies.
Keywords: D23; D83; D92; 330; Task-specific human capital; organizational inertia; time-inconsistency; exploration; exploitation